Analisis Respon Produksi Kopi Di Provinsi Lampung - Irmayani Noer; Agus Agus (Jurnal Ilmiah ESAI, 2007)
Coffee is an agriculture commodity which is has very important meaning for economic in  Lampung.  Based on acreage, coffee plantation in Lampung effort by the most of people traditional farming.   This research was conduct to identify the factors which was influence coffee  production and then to determine coffee production response.  Production, acreage, and productivity condition of coffee on the time series data was analysis with ordinary last square for production elasticity . The analysis showed that  production elasticity value was more than one (EQ,P = 1,349). These condition mean coffee production was responsive with the domestic price change.  If there were coffee domestic price changing will  followed by coffee  production response. While the factors which influence coffee acreage were the last year domestic price, climate,and  the acreage on the year before.  Then, the productivity of coffee determined by three year ago domestic price, coffee acreage, climate, and last year coffee productivity.  Kata Kunci:  respon produksi, luas areal tanam, produktivitas harga domestic,                       elastisitas produksi